2021
DOI: 10.1158/1940-6207.capr-21-0080
|View full text |Cite
|
Sign up to set email alerts
|

“Rescue” of Nonparticipants in Colorectal Cancer Screening: A Randomized Controlled Trial of Three Noninvasive Test Options

Abstract: Few studies have directly targeted nonparticipants in colorectal cancer screening to identify effective engagement strategies. We undertook a randomized controlled trial that targeted nonparticipants in a previous trial of average-risk subjects which compared participation rates for mailed invitations offering a fecal test, a blood test or a choice of either. Nonparticipants (n = 899) were randomized to be offered a kit containing a fecal immunochemical test (FIT), directions on how to arrange a blood DNA test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“… 32 40 To assess acceptability, studies compared participants who had completed a screening intervention or a comparator. Eight studies compared CT colonography and colonoscopy, 20 24 , 34 37 , 38 five studies compared FS and FIT, 25 28 , 39 four studies compared FS and colonoscopy, 21 , 26 , 36 37 four studies compared blood-based biomarker tests and FIT, 29 32 two studies compared colon capsule endoscopy and colonoscopy, 33 , 40 two studies compared CT colonography and FOBT 21 , 23 and one study compared CT colonography and FIT. 24 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 32 40 To assess acceptability, studies compared participants who had completed a screening intervention or a comparator. Eight studies compared CT colonography and colonoscopy, 20 24 , 34 37 , 38 five studies compared FS and FIT, 25 28 , 39 four studies compared FS and colonoscopy, 21 , 26 , 36 37 four studies compared blood-based biomarker tests and FIT, 29 32 two studies compared colon capsule endoscopy and colonoscopy, 33 , 40 two studies compared CT colonography and FOBT 21 , 23 and one study compared CT colonography and FIT. 24 …”
Section: Resultsmentioning
confidence: 99%
“…The results found participants from a higher socio-economic group were more likely to take part in both FS and FIT screening (p < 0.05). Three RCTs 29 31 and one observational 32 study compared uptake of blood-based test and FIT ( Figure 2(c) ). In two of these studies, 29 30 differences in observed uptake were not significant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations